Proses Transaksi Pada Sistem Informasi Akuntansi Serta Implementasinya Pada Perbankan Syariah - Harianto; Rika Lidyah (Yayasan Sagita Akademia Maju, 2025)
This study examines the transaction process in the accounting information system and its implementation in Islamic banking, answering these problems. The author uses this type of research including library research. Library research is a type of research conducted by reading books, journals, or magazines and other data sources to collect data from various literature, both libraries and other places. In this study, the author determines the library research method because there are at least several reasons underlying it. Islamic Bank is a bank based on the principles of partnership, justice, transparency, and universality which are implemented in the form of prohibition of usury in its various forms, Accounting Information from several experts, including According to Nugroho Widjayanto Accounting Information System as follows: